Economic and Social Impacts of Remittances: A Study on Indonesian Migrant Workers' Households - Yolama, Cindy; Alaska, Tegar (Digital Learning, Social Science, and Life-course Studies, 2025)
This study investigates the economic and social impacts of remittances on households of retired Indonesian migrant workers in Nguling and Gondangwetan Districts in 2024. Specifically, it examines: (1) the relationship between remittance utilization and household consumption expenditures, (2) the relationship between remittance utilization and social changes within these families, and (3) the combined effect of remittance utilization and household consumption expenditures on social changes. Using a quantitative approach with a correlation design, the study involved a sample of 95 remittance managers from retired workers' families, selected through purposive area sampling. Data were analyzed via Simple and Multiple Linear Regression using SPSS version 20. The results show: (1) a moderate positive correlation (r = 0.503) between remittance utilization and household consumption, indicating that remittances account for 49.8% of household consumption expenditures; (2) a moderate relationship (r = 0.457) between remittance use and social changes, with remittances influencing 42.8% of these changes; and (3) a significant combined effect of remittance utilization and household consumption expenditures on social changes, as confirmed by an F-value (24.761) exceeding the critical F-table value (3.099). These findings underscore the pivotal role of remittances in shaping economic and social outcomes in the families of retired Indonesian migrant workers.